Evaluating the Financial Solvency of Selected Commercial Banks of Nepal: An Application of Bankometer - Kattel, Indra Kumar (Journal of Advanced Academic Research, 2015)
Banking industry of Nepal is moving towards the goal of integrated financial service because of competition, frequently changes in technology, and customers' expectations. Financial system is reflected through sound solvency position in the banking sector. Therefore, the aim of this study is to evaluate the financial soundness of joint venture banks and private sector banks in Nepal by using bankometer model for the period covering 2007- 2012. The bankometer model was used developed according to International Monetary Fund guidelines. The study has found that all the private and joint venture banks are in sound financial position. The finding of the study reveals that private sector banks are financially sounder in comparison to joint venture banks. The study concludes that bankometer model will help the bank's internal management to mitigate the insolvency risk within proper control and supervision at the operational level.Journal of Advanced Academic Research Vol.1(1) 2014: 88-95